Enhance route discovery Ad hoc On-demand Distance Vector (ERDA) protocol for black hole attack mitigation / Zaid Ahmad - Ahmad, Zaid (2014)
The Ad Hoc routing protocols have an important role in providing end-to-end communication in the Mobile Ad Hoc Networks (MANETs), and Ad hoc On-demand Distance Vector (AODV) is one of them. Unfortunately, the AODV protocol is vulnerable to attacks due to the lack of security. Among various kinds of attacks, the black hole attack is one of the most common attacks made against AODV protocol which consequently received significant interest amongst researchers. One of the solutions to overcome these attacks is by introducing modified AODV that are designed with built-in black hole mitigation feature. The IDSAODV and MOSAODV are among several modified AODV protocols proposed today. However, these protocols have been identified suffer from performance loss, especially during the absence of attacks. In this thesis, an enhanced mitigation mechanism was designed to reduce the risk of performance loss in the absence and presence of the black hole attack, by introducing prevention and alleviation technique and combining them using rt_upd parameter. In order to evaluate the performance loss in the absence of attacks, and to test the effectiveness in the presence of attacks, it was implemented as new modified AODV protocol called ERDA and simulated using the NS-2. Nine network scenarios (without attack) and nine attack scenarios were created in the simulations.Analysis of simulation results showed that in "the absence ofattacks, the differences in terms of PDF and Delay performances between the ERDA and the normal AODV was not statistically significant. Moreover, in the presence of the attack, ERDA worked better than IDSAODV and MOSAODV in mitigating the attack where the ERDA Throughput was significantly higher than IDSAODV and MOSAODV